2003
DOI: 10.1083/jcb.200207096
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in the mobility of LAT in aggregated lipid rafts upon T cell activation

Abstract: Lipid rafts are known to aggregate in response to various stimuli. By way of raft aggregation after stimulation, signaling molecules in rafts accumulate and interact so that the signal received at a given membrane receptor is amplified efficiently from the site of aggregation. To elucidate the process of lipid raft aggregation during T cell activation, we analyzed the dynamic changes of a raft-associated protein, linker for activation of T cells (LAT), on T cell receptor stimulation using LAT fused to GFP (LAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 38 publications
4
60
0
Order By: Relevance
“…Perfringolysin O, a cholesterol-binding toxin produced by Clostridium perfringens, is shown to bind selectively to cholesterol-rich microdomains of intact cells (24). Indeed, the distribution of this toxin showed a patchlike pattern on the cell surface, and LAT-GFP, one of raft markers we have previously reported (19), was clearly colocalized with this site. Thus, cholesterol patches seemed to correspond with lipid rafts, and the formation of cholesterol patches was not inhibited by D-PDMP (Fig.…”
Section: Lipid Raft Organization In D-pdmp-treated Jurkatmentioning
confidence: 82%
See 1 more Smart Citation
“…Perfringolysin O, a cholesterol-binding toxin produced by Clostridium perfringens, is shown to bind selectively to cholesterol-rich microdomains of intact cells (24). Indeed, the distribution of this toxin showed a patchlike pattern on the cell surface, and LAT-GFP, one of raft markers we have previously reported (19), was clearly colocalized with this site. Thus, cholesterol patches seemed to correspond with lipid rafts, and the formation of cholesterol patches was not inhibited by D-PDMP (Fig.…”
Section: Lipid Raft Organization In D-pdmp-treated Jurkatmentioning
confidence: 82%
“…The XhoI/NotI fragment was then cloned into the pMX-puromycin retroviral vector (17). The resulting construct (pMX-Thy-1) was expressed in J.EcoR cells via retrovirus infection as described previously (18,19). For stable transfectants, the infected cells were selected in medium supplemented with puromycin at 0.4 g/ml from 48 h after infection.…”
Section: Methodsmentioning
confidence: 99%
“…Second, imaging approaches using planar substrates demonstrated that LAT variants with mutated tyrosines in the cytoplasmic tail were not recruited to signaling microclusters (Douglass and Vale 2005;Bunnell et al 2006;Houtman et al 2006). Finally, single particle tracking techniques as well as FRAP methods that measured diffusion rates of LAT revealed that LAT cytoplasmic tyrosines are required for confinement of LATwithin transient subdomains (Tanimura et al 2003b;Douglass and Vale 2005). In contrast, interfering with lipid raft association of LAT through mutations did not alter its diffusion behavior (Douglass and Vale 2005).…”
Section: Mechanisms Of Assembly Of Lat Clusters and Lat-nucleated Commentioning
confidence: 99%
“…This method allows evaluation of mobility and population-level diffusion dynamics of molecules (Tanimura et al 2003a). Studies on LAT dynamics at the membrane revealed the fast exchange of molecules between LAT clusters or patches localized at sites of stimulation (Tanimura et al 2003b;Douglass and Vale 2005). Single-molecule imaging studies have revealed that LAT molecules at the plasma membrane display abrupt changes between immobility and rapid diffusion (Douglass and Vale 2005).…”
Section: Lat Microclusters: Sites Of Nucleation Of Signaling Complexesmentioning
confidence: 99%
“…Immunomagnetic microsphere separation and microparticle based flow cytometry play an important role in experimental protocols and analytical procedures (19,20). Recently, microspheres have also served as powerful tools for studying complex cell biological phenomena such as collagen phagocytosis in fibroblasts (21,22), viscoelastic responses of endothelial cells upon thrombin stimulation measured by magnetic microsphere-based microrheology (23), and re-organization of lipid rafts and signalling complexes upon various stimuli (24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%